Evolution of Heat Wave Monitoring and Forecasting in India - Mohapatra, M.; Srivastava, Akhil; Nadimpalli , Raghu; Kumar , Naresh (MAUSAM, 2025)
The article describes the journey of India Meteorological Department as a nodal agency with respect to weather related aspects since its inception through the lens of Heat Wave forecasting and warning services. It deals with the evolution specific to India in terms of heat waves definitions, scientific understanding, researches and operational forecasting methodologies during the past 150 years. The article also touches upon the current situation of the monitoring and forecasting strategies, tools and techniques followed by IMD with respect to Heat Wave impact based early warning and forecasting services.